Moral competence and conduct disorder among Filipino children in conflict with the law - Melissa Paulita V. Mariano (Wiley, 2019)
Abstract Aims The numbers of children in conflict with the law continue to rise in Asia, yet few studies have been conducted regarding factors associated with it. It has been theorized that children with conduct disorder represent majority of children in conflict with the law, and that poor moral competence mediates the association between conduct disorder and antisocial behavior. This study aimed to present a profile of Filipino children in conflict with the law, determine the prevalence of conduct disorder in the sample, and investigate variables associated with conduct disorder. Methods This was a cross‐sectional study conducted at a conflict with the law Custodial Care Center in the Philippines. The procedure entailed a diagnostic interview and questionnaire administration conducted by psychiatrists. Questionnaires administered included the Moral Competence Test and Parental Warmth and Acceptance Scale. Statistical analyses of data included descriptive statistics, chi‐square tests, and independent t tests. SPSS v.23.0 was used for data encoding and analysis. Results Twenty‐three participants were included in the study, with 10 participants with conduct disorder and 13 controls. Majority were male adolescents between the ages of 16 and 18 years. Conduct disorder was associated with commission of multiple violations, particularly theft and homicide, the presence of a substance use disorder, and a history of abuse. Participants with conduct disorder had lower moral competence levels compared to participants without conduct disorder. Conclusion Conduct disorder was associated with high‐risk antisocial behavior and lower levels of moral competence.